2018
DOI: 10.3144/expresspolymlett.2018.76
|View full text |Cite
|
Sign up to set email alerts
|

A study on the effects of graphene nano-platelets (GnPs) sheet sizes from a few to hundred microns on the thermal, mechanical, and electrical properties of polypropylene (PP)/GnPs composites

Abstract: Polypropylene (PP) is incorporated with four different grades (H100, M25, M5, and C300) of graphene nanoplatelets (GnPs) via twin screw extrusion followed by injection moulding. The composites' thermal stability, crystallization behaviour, tensile strength, and electrical property are carefully examined. The thermal stability is significantly enhanced with the incorporation of small-sized GnPs as shown by the 11.2% improvement in T 5% (the temperature at which 5 wt% of the mass loss occurs) and 5.1% improvemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 36 publications
12
59
0
Order By: Relevance
“…However, it could be associated with the existence of a multi-step percolation behavior where a tunneling mechanism dominates the current flow between the conductive particles [46,55]. Most importantly, the percolation threshold reported in this study is significantly lower than those reported previously for polypropylene [40,41,56] using melt mixing methods [27] and other similar polymers [57]. An overview of the reported electrical percolation values for a number of different polypropylene/graphene systems prepared with various melt mixing protocols is presented in Table 1.…”
Section: Electrical Conductivitymentioning
confidence: 55%
See 4 more Smart Citations
“…However, it could be associated with the existence of a multi-step percolation behavior where a tunneling mechanism dominates the current flow between the conductive particles [46,55]. Most importantly, the percolation threshold reported in this study is significantly lower than those reported previously for polypropylene [40,41,56] using melt mixing methods [27] and other similar polymers [57]. An overview of the reported electrical percolation values for a number of different polypropylene/graphene systems prepared with various melt mixing protocols is presented in Table 1.…”
Section: Electrical Conductivitymentioning
confidence: 55%
“…This behavior can be associated with nucleation effects and has been reported in the past for a number of fillers including clay, nanotubes and graphitic platelets [35,61,62]. Polypropylene has a very rich polymorphism form and it has been reported that filler inclusion has an effect of the overall morphology of the system [56]. For this reason, we have investigated the effect of the filler in the overall crystallinity and the resulting morphology.…”
Section: Morphologymentioning
confidence: 70%
See 3 more Smart Citations